Revitalisasi Sekolah Minggu di Gereja Toraja Nonongan Salu - Aussie Femy Tangdilintin; Salmon Pamantung (SERVIRE: Jurnal Penelitian dan Pengabdian, 2025)
This research was motivated by the decrease in children's participation and enthusiasm in participating in Sunday School activities at the Toraja Nonongan Salu Church. Sunday School, which was once the main forum for the formation of children's faith, is now experiencing stagnation in methods and materials. This study uses a qualitative literature method, by reviewing the literature related to the revitalization of children's ministry, ecclesiastical education, and contextual approaches in spiritual formation. Supporting data was obtained through direct observation and limited interviews with church administrators. The results showed that 62% of children aged 6–12 years in the congregation were not actively present in the last 3 months. The main factors found include a lack of innovation in learning methods, a lack of teacher training, and children's lack of interest in monotonous worship patterns. Revitalization through creative approaches, teacher training, and contextualization of materials has been proven to increase child engagement by up to 40%. Thus, the revitalization of Sunday School is a strategic step to strengthen the development of children's faith in the local church. Penelitian ini dilatarbelakangi oleh menurunnya partisipasi dan semangat anak-anak dalam mengikuti kegiatan Sekolah Minggu di Gereja Toraja Nonongan Salu. Sekolah Minggu yang dulunya menjadi wadah utama pembentukan iman anak, kini mengalami stagnasi dalam metode dan materi. Penelitian ini menggunakan metode kualitatif kepustakaan, dengan mengkaji literatur terkait revitalisasi pelayanan anak, pendidikan gerejawi, serta pendekatan kontekstual dalam pembinaan rohani. Data pendukung diperoleh melalui observasi langsung dan wawancara terbatas kepada pengurus gereja. Hasil penelitian menunjukkan bahwa 62% anak-anak usia 6–12 tahun di jemaat tersebut tidak aktif hadir dalam 3 bulan terakhir. Faktor utama yang ditemukan meliputi kurangnya inovasi dalam metode pembelajaran, minimnya pelatihan guru, serta ketidaktertarikan anak pada pola ibadah yang monoton. Revitalisasi melalui pendekatan kreatif, pelatihan guru, dan kontekstualisasi materi terbukti mampu meningkatkan keterlibatan anak hingga 40%. Dengan demikian, revitalisasi Sekolah Minggu merupakan langkah strategis untuk memperkuat pembinaan iman anak di gereja lokal.